In vitro Embryo Morphogenesis and Micropropagation of Dendrobium aggregatum Roxb. - Hossain, Mohammad Musharof (Plant Tissue Culture and Biotechnology, 2014)
In vitro embryo morphogenesis and micropropagation of Dendrobium aggregatum Roxb. were described. The gradual developmental stages of embryos to seedlings were traced out. Within two weeks of culture the cells of undifferented embryos underwent repeated aniclinal and periclinal division producing a compact, green parenchymatous cell mass called spherule that emerged out by rupturing the testa. The spherules subsequently differentiated into greenish protocorms were considered as typical seed germination. Germination occurred on both (MS and Phytamax (PM) medium but MS medium proved to be more efficient. The primary protocorms underwent profuse proliferation through production of secondary (2º) protocorms when transferred to different plant growth regulators (PGRs) supplemented MS; the medium fortified with 2.0 mg/l BAP and 1.0 mg/l NAA proved to be most effective for induction of 2º protocorms and seedling development. Multiple shoot buds (MSBs) were induced in pseudobulb segments of the in vitro grown seedlings when cultured on different PGRs supplemented media; and the maximum number of MSBs were obtained MS + 2.0 mg/l BAP + 0.5 mg/l picloram. The MSBs underwent elongation and then they rooted when they were transferred to half strength of MS + 0.5 mg/l IAA. The well rooted plantlets were finally transferred to outside natural environment with 80% survival. D. O. I. http://dx.doi.org/10.3329/ptcb.v23i2.17525 Plant Tissue Cult. & Biotech. 23(2): 241-249, 2013 (December)